Steric exclusion chromatography: Advancement of a laboratory-based platform technology into a key component of viral vector and vaccine production processes - Lothert, Keven; Justus Liebig University Giessen (My University, 2021)
Biological macromolecules, such as viruses, virus-like particles or extracellular vesicles represent an important and permanently growing element in the biopharmaceutical industry. These macromolecules applied as pharmaceutical products have proven suitable for prophylactic or therapeutic vaccination, oncolytic therapy or gene transfer, to name only a few. Beside the challenge of producing sufficient amounts of product, its purification during the downstream processing, for example from cell culture harvests, is of major importance to allow a safe and efficient application. A large variety of particles differing in their physicochemical properties, possibly affecting their stability and their interaction with surrounding molecules, requires multifaceted processing strategies. For this reason, purification process development can be a time and cost consuming element, which emphasizes the benefits of flexible techniques that can be applied to a variety of different products. Over the past ten years the steric exclusion chromatography (SXC) was introduced as a possible platform technique for a fast and effective purification of macromolecules and nanoplexes such as large proteins, bacteriophages, and viruses. The technique was derived from the principle of polymer induced crowding mechanisms, that are already known for several decades. Although the method highly depends on the size of the target product, all the influencing process parameters and mechanisms of the method are not yet thoroughly understood. The SXC has been applied as an independent process unit operation but has not been implemented in large scale biopharmaceutical production. The latter can be mainly attributed to the novelty of the principle, the lack of appropriate stationary phases suitable for industrial production, and an inherent skepticism against new approaches compared to established and regulatory accepted procedures. This work aims to bridge laboratory applications of the SXC with scaled approaches of up to 200 L by suggesting possible processing schemes employing that technique as a major purification backbone. Simultaneously, these studies provide further insight into critical process parameters to allow for an improvement of the mechanistic understanding concerning the method itself. In the chapters of this work the successive implementation of the SXC into complete downstream processing schemes for viral vectors and vaccines is shown. While Chapter 1 gives an overview to introduce the importance of improving and extending the existing portfolio of purification procedures, it also introduces the benefits of applying platform technologies. Particularly the principle and advantages of the SXC are described as well as the scope of this thesis is outlined. Chapter 2 summarizes the general approach for applying and optimizing the SXC using the baculovirus vector as a model and Chapter 3 shows a screening comparison of the SXC against and in combination with well-known purification techniques. Afterwards, in Chapter 4, the platform applicability in complete processing schemes is shown for Hepatitis C and Orf virus purification targeting potential applications in human or veterinary medicine. Finally, Chapter 5 gives a short summary, including an outlook on future prospects and remaining hurdles.
Keywords: Downstream processing; Virus purification; Steric exclusion chromatography; Vaccine production; ddc:500; ddc:570; ddc:620